Glutathione-S-transferases M1/T1 gene polymorphisms and male infertility risk in Chinese populations: A meta-analysis. Issue 6 (February 2019) - Hu, Chun-Yan; Lu, Dong-Liang; Wu, Tao; Cheng, Shu-Lin; Wu, Tian-tian; Wang, Shu; Zhang, Tao
Abstract: Background: A meta-analysis was applied to evaluate the associations between the glutathione-S-transferases (GSTs) M1/T1 gene polymorphisms and male infertility in Chinese populations. Methods: A comprehensive search for articles was conducted from PubMed, Web of Science, Embase, China biology medical literature database (CBM), China National Knowledge Infrastructure (CNKI), VIP, and Chinese literature database(Wang fang) up to April 30, 2018. All of the statistical analyses were performed using Review Manager 5.3 and Stata 14.0. Results: Ten studies on GSTM1 gene polymorphism involving 3302 cases and 1959 controls, and ten studies on GSTT1 gene polymorphism involving 3048 cases and 1861 controls were included in this meta-analysis. Overall, the null genotype of GSTM1/GSTT1 was significantly related to male infertility risk in Chinese populations ( GSTM1, OR = 1.35, 95% CI: 1.02–1.78; GSTT1, OR = 1.40, 95% CI: 1.15–1.70). In subgroup analyses stratified by infertility type, significant association was observed between GSTT1 null genotype and male infertility in both nonobstructive azoospermia (NOA) and oligoasthenozoospermia (OAT). However, the GSTM1 null genotype was associated with OAT, but not NOA in Chinese populations. The sensitivity analysis confirmed the reliability and stability of the meta-analysis. Conclusion: Our meta-analysis supports that the GSTM1/GSTT1 null genotype might contribute to individual susceptibility to male infertility in Chinese populations.